Próba określenia czynników determinujących decyzje spółek o wypłacie dywidend na warszawskiej Giełdzie Papierów Wartościowych - Kowerski, Mieczysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In 2002 22,7% of companies quoted on Warsaw Stock Exchange paid dividends. Likelihood of paying dividend increased together with the increase of the size of firm measured by the book and market value, profitability and the earnings - price ratio. More likely to pay dividends were the firms with higher level of corporate governance. Firms paying dividends were also characterized by higher returns and lower risk measured by the variability of stocks. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 164-172